2002
DOI: 10.1080/09638280210142176
|View full text |Cite
|
Sign up to set email alerts
|

Improving the physician role in evaluating work ability and managing disability: a survey of primary care practitioners

Abstract: Evaluations of work status and work ability are common PCP activities, but little formal training has been provided in this area. Rehabilitation professionals can have a significant role through provider education, developing improved systems for communication with employers, and encouraging employers to provide more alternative duty assignments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 20 publications
4
48
0
1
Order By: Relevance
“…Similar findings were made in a study by Pransky and colleagues [17] where the physicians reported barriers in helping the patient return to work, such as long-term sick leave requests, mental disorders, conflict with the employer, and work dissatisfaction [17]. According to previous research, individuals with older age, history of previous sick leave, worse mental and physical functioning, negative expectation of recovery, lower socio-economic status, and impaired work ability are at increased risk for long-term sick leave.…”
Section: Handling Sickness Certificationssupporting
confidence: 80%
See 3 more Smart Citations
“…Similar findings were made in a study by Pransky and colleagues [17] where the physicians reported barriers in helping the patient return to work, such as long-term sick leave requests, mental disorders, conflict with the employer, and work dissatisfaction [17]. According to previous research, individuals with older age, history of previous sick leave, worse mental and physical functioning, negative expectation of recovery, lower socio-economic status, and impaired work ability are at increased risk for long-term sick leave.…”
Section: Handling Sickness Certificationssupporting
confidence: 80%
“…Physicians are responsible for documenting work demands in sickness certificates, but our findings indicate that physicians and other healthcare professionals have sparse knowledge regarding work demands, and insufficient prerequisites to contact the employer. This supports earlier studies reporting that direct contact with the employer is rare [17,21,37,5], and that physicians rely on patients' self-reports of working conditions and available work modifications rather than obtaining information from the employer [17]. The limited contact with the employer might have implications for patients' return to work.…”
Section: Collaborationsupporting
confidence: 75%
See 2 more Smart Citations
“…Also, most did not have contacts with patients' employers (Table 2). According to previous studies, physicians instead often rely on patients' self‐reports of working conditions rather than obtaining information direct from the employer (Edlund & Dahlgren, 2002; Pransky, Katz, Benjamin, & Himmelstein, 2002). Limited knowledge about work demands might delay the return to work since lack of workplace information gives less opportunity to discuss adjustments of work tasks in relation to the patient's current function.…”
Section: Discussionmentioning
confidence: 99%